Digital transformation and the COVID-19 crisis continuity planning. Issue 2 (November 2021) - Datta, Pratim; Nwankpa, Joseph K
The unprecedented global lockdown during the COVID-19 pandemic has highlighted an interesting ethical dilemma. While lockdowns are central to saving lives, economic malaise from business and social discontinuities is the opportunity cost. To maintain this fragile balance during a crisis, there is an obvious need for digitally transforming socio-economic operations to maintain continuity. This digital transformation case study highlights how, unlike traditional digital transformation initiatives that rely on relatively closed organizational operations with established lines of control and communication, digital transformation for crisis continuity planning relies on a variety of global actors, from independent entrepreneurs and institutions to businesses and ad hoc collaborative agencies. The crisis continuity planning case helps students understand that digital transformation is a multi-stakeholder, multi-actor effort that ties together technology, business process reengineering, and public policy for a sustainable solution to a crisis. This teaching case study end with a proposed crisis continuity planning digital transformation framework that outlines five distinct digital transformation characteristics that can improve crisis continuity planning—from pandemics to disasters.